Does Organic Wine Taste Better? An Analysis of Experts' Ratings*. (2nd August 2016) - Delmas, Magali A.; Gergaud, Olivier; Lim, Jinghui
Abstract: Ecolabels are part of a new wave of environmental policy that emphasizes information disclosure as a tool to induce environmentally friendly behavior by both firms and consumers. Little consensus exists as to whether ecocertified products are actually better than their conventional counterparts. This study seeks to understand the link between ecocertification and product quality. We use data from three leading wine-rating publications (the Wine Advocate, Wine Enthusiast, and Wine Spectator ) to assess quality for 74, 148 wines produced in California between 1998 and 2009. Our results indicate that ecocertification is associated with a statistically significant increase in wine quality rating. Being ecocertified increases the scaled score of the wine by 4.1 points on average. (JEL Classifications: L15, L66, Q13, Q21, Q56)